LEXICONS OF FAUNA IN BATAK TOBA UMPASA: A STUDY OF ECOLINGUISTICS - Devi Melisa Saragi (Jurnal Scientia, 2022)
Ecolinguistics is a study dealing the physical and social ecological context where language operates, and in turn, how language and discourse affect the environment and ecology. This research tried to determine the kinds of fauna found in constructing umpasa, the functions of the fauna lexicons as the lingual units in constructing the umpasa and the philosophical value which is represented by the lexicons of fauna in umpasa. Umpasa is a Batak Toba poem consisting of two, three, four lines or more conveyed by the people having higher position in the Batak kinship system. This research applied the qualitative descriptive with content analysis approach. The object of the data was the umpasa containing lexicons of fauna which were collected by observing method and note taking techniques. All the data obtained were then analyzed by content analysis approach. The first result of this research shows that the fauna found in umpasa are birds (olive-winged bulbul, sparrows, turtledoves), snakes, fish, buffaloes, cows, mice, insect , while the second result are that syntactically, the lexicons of fauna constructing the umpasa stand as subject, subject with implicit verb and object (direct and indirect object).The third result represents that the lexicons of fauna found in umpasa actually distribute some of philosophical value, such as value of environmental philosopy, value of transportation philosophy, value of cultural and traditional philosophy, value of consumption philosophy, value of high social status in the society, and value of health philosophy.